The association of perceived leadership style and subjective well-being of employees in a tertiary hospital in Germany - Erschens, Rebecca; Seifried-Dübon, Tanja; Stuber, Felicitas; Rieger, Monika A.; Zipfel, Stephan; Nikendei, Christoph; Genrich, Melanie; Angerer, Peter; Maatouk, Imad; Gündel, Harald; Rothermund, Eva; Peters, Martin; et al. (PLOS ONE, 2022)
Background Professionals in the healthcare sector are a particularly vulnerable group for occupational strain due to high work-related psychological stress. For the implementation of targeted stress-prevention interventions as an important part of a workplace health management programme for all occupational groups and hierarchy levels, information about the current state of their mental health is mandatory. Hence, this study investigated the association of general well-being and different leadership styles among employees in a German tertiary hospital. Methods Via an online survey, 10,101 employees were contacted. The final sample consisted of 1137 employees. Of these, 27.7% described themselves as leaders and 72.3% as followers. Most participants were female (74.8%), more than half were under 41 years old. Besides control variables, general well-being (WHO-5) and leadership style (transactional and transformational, laissez-faire and destructive leadership) were assessed. Results Leaders reported higher well-being scores than followers. Physicians without leadership responsibilities had the lowest scores for well-being. Practitioners of both transformational and transactional leadership were associated with higher well-being scores, while those practicing laissez-faire and destructive leadership had lower scores for almost every professional group. Conclusion Results highlight the necessity for future multimodal health-preventive leadership interventions feature behavioural and organizational intervention modules specifically tailored to hospital professionals at different hierarchical and functional levels to foster the mental health of employees.
Gesehen am 02.05.2022